1996
DOI: 10.1172/jci119003
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of extracellular matrix by mechanical stress in rat glomerular mesangial cells.

Abstract: Increases in intraglomerular pressure are known to predispose to the development of glomerular sclerosis, which is characterized by accumulation of extracellular matrix within the glomerulus. Glomerular mesangial cells are exposed to pulsatile capillary pressures and are a potential target for mechanical stress. In the present studies, we subjected cultured rat mesangial cells to continuous cycles of stretching and relaxation (stretch/relaxation) and examined alterations in extracellular matrix gene expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
92
1
4

Year Published

1998
1998
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(108 citation statements)
references
References 45 publications
11
92
1
4
Order By: Relevance
“…Mechanical stretch has been shown to increase TGF-␤1 production and secretion in MC and other cells (7,8,73), and this cytokine plays an important role in stretch-induced upregulation of matrix proteins including collagen I (8,74). Our data have further demonstrated that collagen I protein secretion into the medium also requires the autocrine action of TGF-␤1.…”
Section: Discussionsupporting
confidence: 63%
“…Mechanical stretch has been shown to increase TGF-␤1 production and secretion in MC and other cells (7,8,73), and this cytokine plays an important role in stretch-induced upregulation of matrix proteins including collagen I (8,74). Our data have further demonstrated that collagen I protein secretion into the medium also requires the autocrine action of TGF-␤1.…”
Section: Discussionsupporting
confidence: 63%
“…On the other hand, mechanical stretch and high glucose directly stimulate Tgfb1 expression and TGFB1 production in cultured mesangial cells, resulting in collagen accumulation [33][34][35][36]. These results indicate that metabolic and haemodynamic changes may also induce extracellular matrix accumulation independently of inflammation in the development of diabetic glomerulosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that mesangial cells exposed to continuous cycles of stretch/relaxation increase gene and/ or protein expression of extracellular matrix components, including fibronectin, collagen I, III and IV and laminin. 39 Furthermore, this accumulation of extracellular matrix, which occurs as a result of mechanical stretch, is markedly enhanced in a milieu of high glucose concentration. 40 Of interest here is that mechanical stretch may promote extracellular matrix accumulation in cultured mesangial cells, not only by increasing synthesis of extracellular matrix components, but also by decreasing the activity of degradative enzymes.…”
Section: In Vitro Studies Searching For the Mechanism Of The Interactmentioning
confidence: 99%
“…40 Of interest here is that mechanical stretch may promote extracellular matrix accumulation in cultured mesangial cells, not only by increasing synthesis of extracellular matrix components, but also by decreasing the activity of degradative enzymes. 39 In addition, mechanical stretch induces both gene and protein expression of transforming growth factor (TGF)-b1, 39,41 a cytokine involved in the accumulation of extracellular matrix in diabetic nephropathy. 41 Mechanical stretch has also been shown to induce gene expression, but not protein secretion of connective growth factor, a downstream mediator of TGF-b1 signaling.…”
Section: In Vitro Studies Searching For the Mechanism Of The Interactmentioning
confidence: 99%